PELATIHAN PERANCANGAN KEMASAN UNTUK MENINGKATKAN KUALITAS PRODUK DI PABRIK KRUPUK SGM - Tri Wisudawati; Ecclisia Sulistyowati (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
Various facilities that are felt in utilizing information technology in the industry are very helpful in marketing activities ranging from marketing products, finding customers to buying and selling transactions that can increase competitiveness so that it can develop more rapidly. The development of technology in facing business competition is so rapid, especially in the field of marketing, so that the home industry business "SMG Crackers Factory" has not used marketing strategies to increase the product brand and sales of these crackers. The development of technology here is the development of information innovation in marketing. The SMG Crackers Factory only becomes a distributor who distributes the crackers daily to the seller of mobile crackers in a makeshift packaging such as a tin jar box. So we will provide training to owners and employees in increasing product innovation by using the 4P marketing mix method, namely Product, Price, Place, and Promotion. As a result of this community service, SMG crackers factories can market their products maximally in various market segments through product designs that contain company brand information and can market products with more variety and attract consumers.